Fighting the hepatitis B virus: past, present & future - Tan, Wen Siang (Universiti Putra Malaysia Press, 2016)
Hepatitis B virus (HBV) is one of the greatest killers of human beings. The production of recombinant HBV vaccine via genetic engineering and mass immunization of the world population with the vaccine have had huge success in bringing down the number of infected people. However, until now there is no effective treatment for HBV infections. Nucleoside analogues are commonly used to treat chronic hepatitis B patients, but prolonged treatments have resulted in the selection of drug resistant strains and vaccine escape mutants. More importantly, HBV is linking arms with the human immunodeficiency virus (HIV) to kill more humans. Many dedicated scientists and highly motivated doctors have risked their lives to control the spread of HBV and search for a cure for this deadly virus. Their ultimate goal is to eradicate the virus from this planet and make the world a better place for everyone. Therefore, the main aim of this talk is to provide a comprehensive review of their contributions in the development of vaccines, diagnostic assays, therapeutics and drug delivery systems to fight HBV.